1993
DOI: 10.1002/ajh.2830440109
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive chemoimmunotherapy using Ex vivo activated memory T‐cells and cyclophosphamide: Tumor lysis syndrome of a metastatic soft tissue sarcoma

Abstract: Adoptively transferred immune cells in combination with chemotherapeutic agents form the basis for adoptive chemoimmunotherapy (ACIT) of neoplastic disease. Autolymphocytes (ALT-cells) are ex vivo activated peripheral blood lymphocytes (PBL) from tumor-bearing hosts (TBH) that consist primarily of tumor-specific CD45RO+ (memory) T-cells. These ALT-cells combined with cimetidine (CIM) as autolymphocyte therapy (ALT), have previously been demonstrated to be a safe and active form of outpatient adoptive immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…All of the patients had evidence of advanced and metastatic disease. One patient was reported to have normal baseline laboratory values, 111 one had elevated baseline values of creatinine and phosphorus, 112 and another one had baseline values for elevated levels LDH. 113 Three cases were associated with preceding chemotherapy.…”
Section: Tumor Lysis Syndrome In Sarcomasmentioning
confidence: 99%
“…All of the patients had evidence of advanced and metastatic disease. One patient was reported to have normal baseline laboratory values, 111 one had elevated baseline values of creatinine and phosphorus, 112 and another one had baseline values for elevated levels LDH. 113 Three cases were associated with preceding chemotherapy.…”
Section: Tumor Lysis Syndrome In Sarcomasmentioning
confidence: 99%
“…According to the literature review, there have been 100 reported cases of TLS in patients with solid tumors from the first report in 1977 to 2011 (Table 1) (Figure 2), including small cell carcinomas [9, 2030], squamous cell carcinomas [10, 11], adenocarcinomas of the lung [12, 3133], mixed small cell and nonsmall cell lung carcinoma [34], gastrointestinal carcinomas [1315, 3542], hepatoblastomas [43, 44], hepatocellular carcinomas [15, 4553], renal carcinomas [54–56], transitional cell carcinoma [57], prostate carcinomas [5861], breast carcinomas [16, 30, 62–68], ovarian carcinomas [69, 70], endometrial carcinoma [71], vulva carcinomas [72, 73], thymomas [74, 75], melanomas [76–82], gestational trophoblastic neoplasia [83], germ cell tumors [17, 18, 64, 84, 85], neuroblastomas [86, 87], medulloblastomas [88, 89], and sarcomas [19, 9093]. Most cases regarded as TLS in solid tumors were chemotherapy-induced, even though various other causes were pointed out for TLS in solid tumors as well [3] (Table 1) (Figure 1).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Solid tumors that are known to cause TLS include breast carcinoma [3], medullo-blastoma [4], ovarian cancer [5], rhabdomyosarcoma [6] and neuro-blastoma [7]. Typically these tumors are bulky with multiple metastatic foci and generally are sensitive to initial chemotherapy.…”
Section: Discussionmentioning
confidence: 99%